Magulang Bilang Guro: Parents’ Experiences as Co-Teaching Parents Dur-ing Modular Distance Learning - De Ungria, Celeste F. (Future Science / FSH-PH Publications, 2023)
This study basically investigated the experiences of parents as facilitators of learning as Lagundi-CCL NHS implemented modular distance learning, S.Y. 2021-2022. Twenty (20) parents were considered as respondents in the study. They were chosen purposively by the researcher as she knows them personally. These parents were all the grade level. Utilizing the phenomenological method of inquiry, the parents were interviewed getting their narratives and recommendations as co-teaching parents. Based on the interview, the following themes were derived 1) Motivating their children to pursue education; 2) Mentoring their children in answering the modules; 3) Character building and setting goals in life while learning at home; and 4) Self-realization and reflections. Moreover, their recommendations included: a) to lessen the activities; b) conduct of online classes; and c) implementation of face-to-face classes.